Analisis manajemen risiko transformasi digital di lembaga keuangan syariah: pendekatan studi kasus dan regulasi nasional - Afrizal, Nova Maulana (Maliki Interdisciplinary Journal, 2025)
his study aims to analyze the interrelation between digital transformation, digital risk management, and the performance of Islamic financial institutions, while identifying key risks and mitigation efforts involved in the digitalization process. A qualitative literature-based approach is used, drawing from recent academic journals. The findings reveal that the success of digitalization is closely tied to infrastructure readiness, risk awareness culture, and alignment of technology with Sharia principles. Key risks identified include data security threats, system failures, and potential non-compliance with Islamic values. To address these issues, institutions are advised to implement mitigation strategies that involve information system protection, human resource training, and the integration of regulations with Sharia supervision. The study highlights that successful digital transformation relies not only on technological adoption, but also on strategic risk management aligned with Islamic ethics.